Some results on (δ-pre, s)-continuous functions - Adem Kiliçman; Zabidin Salleh (International Journal of Mathematics and Mathematical Sciences)
We study some properties of (δ-pre, s)-continuous functions. Basic characterizations and several properties concerning (δ-pre, s)-continuous functions are studied. The general cases for the composition of functions under specific conditions which yield (δ-pre, s)-continuous functions are also studied and we obtained some results.